2020
DOI: 10.1007/s10458-020-09447-w
|View full text |Cite
|
Sign up to set email alerts
|

Facial feedback for reinforcement learning: a case study and offline analysis using the TAMER framework

Abstract: Interactive reinforcement learning provides a way for agents to learn to solve tasks from evaluative feedback provided by a human user. Previous research showed that humans give copious feedback early in training but very sparsely thereafter. In this article, we investigate the potential of agent learning from trainers' facial expressions via interpreting them as evaluative feedback. To do so, we implemented TAMER which is a popular interactive reinforcement learning method in a reinforcement-learning benchmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Li et al trained a mapping model that can map implicit emotions to different explicit feedback data. Facial expressions were marked with different types of feedback in advance, such as 1 for "happy", 0 or -1 for "sadness" [40]. Based on this work, Gadanho introduced a facial feedback reinforcement learning method, which is based on an emotion recognition system.…”
Section: Implicit Interactive Methodsmentioning
confidence: 99%
“…Li et al trained a mapping model that can map implicit emotions to different explicit feedback data. Facial expressions were marked with different types of feedback in advance, such as 1 for "happy", 0 or -1 for "sadness" [40]. Based on this work, Gadanho introduced a facial feedback reinforcement learning method, which is based on an emotion recognition system.…”
Section: Implicit Interactive Methodsmentioning
confidence: 99%
“…Li et al trained a prediction model mapping the facial feedback to explicit keypress feedback with collected data. Their simulated experiment showed that with enough recognition accuracy, agents can learn a comparative performance from solely facial feedback compared to learning from explicit keypress feedback [50].…”
Section: ) Natural Interactionmentioning
confidence: 99%
“…In addition, these natural interactive feedback can even be combined with hardware delivered feedback to train agents. For example, Li et al mapped the facial expressions to explicit keystroke feedback and proposed to allow an agent to learn from both the predicted facial feedback and keystroke feedback [50].…”
Section: B Multimodal Sensory Feedbackmentioning
confidence: 99%
“…Our work relates closely to the growing literature of interactive reinforcement learning (RL), or humancentered RL [2,21,22,23,24,25,26,27,28,29] , in which agents learn from interactions with humans in addition to, or instead of, predefined environmental rewards. In the EMPATHIC framework, we use the term implicit human feedback to refer to any multi-modal evaluative signals humans naturally emit during social interactions, including facial expressions, tone of voice, head gestures, hand gestures and other body-language and vocalization modalities not aimed at explicit communication.…”
Section: Related Workmentioning
confidence: 99%